Animal performance, yield and characteristics of the meat of quail fed diets containing vegetable and mixed glycerin - Farrapo, Samily de Paulo; Alves, Marcio Gleice Mateus; Brito, Jéssica de Carvalho; Batista, Ana Sancha Malveira; Freitas, Ednardo Rodrigues; Nascimento, Germano Augusto Jerônimo do (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effect of the inclusion of vegetable and mixed glycerin in the diet of broiler quail (Coturnix coturnix coturnix) on animal performance, yield of carcass and organs, and physical and sensory characteristics of the meat. A total of 432 quails aged 1–42 days were used in a completely randomized design with a 4×2+1 factorial arrangement (5, 10, 15, and 20% inclusion of vegetable or mixed glycerin, besides one treatment without glycerin) with 4 replicates of 12 birds each. Feed intake, weight gain, feed conversion, yield (carcass, breast, thigh+drumstick, heart, liver, gizzard, and abdominal fat), and physical and sensory characteristics of the meat. The diet containing mixed glycerin resulted in higher feed intake and feed conversion. The yield of carcass, meat cuts, and organs, as well as the sensory characteristics of the meat, did not vary between the treatments. Abdominal fat content and shear strength were higher in birds fed diets containing vegetable glycerin. The tested glycerin and levels do not interfere with weight gain, yield, and sensory quality of the meat. However, weight gain and feed conversion are lower when mixed glycerin is used, although meat tenderness is higher when 15% vegetable glycerin is used.
Keywords: Coturnix coturnix coturnix; carcass yield; meat quality; weight gain